SKRINING FITOKIMIA DAN UJI ANTIBAKTERI EKSTRAK ETANOL DAUN HANJUANG MERAH (Cordyline fruticose) TERHADAP BAKTERI Staphylococcus epidermidis - Ayuchecaria, Noverda; Oksal, Efriyana; Sri Martani, Natalia; Kartika Komara, Nisa; Chuchita; Pereiz, Zimon (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Hanjuang Merah (Cordyline fruticosa) is one of the plants used by the Dayak people as traditional medicine. Red hanjuang is an ornamental plant that is very abundant in Indonesia, but there is still not much research that proves the efficacy of red hanjuang. The aim of this research was to determine the phytochemical screening and antibacterial activity of leaf extract of hanjuang merah (Cordyline fruticose) against the bacteria Staphylococcus epidermidis. The method used in sample extraction was maceration, while in the antibacterial test used the paper strip diffusion method with concentrations of 25%, 50%, 75% and 100%. The yield of ethanol extract of hanjuang merah leaf was 11.35%. There was an increase in the diameter of the inhibition zone with the addition of the concentration of ethanol extract of hanjuang merah leaf. The addition of ethanol extract of hanjuang merah leaf at a concentration of 75% sensitive inhibited the growth of Staphylococcus epidermidis bacteria. Secondary metabolites such as tannins, alkaloids, saponins, flavonoids and quinones found in ethanol extract of hanjuang merah leaves are considered responsible for inhibiting the growth of Staphylococcus epidermidis bacteria.